2021
DOI: 10.1016/j.media.2021.102159
|View full text |Cite
|
Sign up to set email alerts
|

Weakly unsupervised conditional generative adversarial network for image-based prognostic prediction for COVID-19 patients based on chest CT

Abstract: Because of the rapid spread and wide range of the clinical manifestations of the coronavirus disease 2019 (COVID-19), fast and accurate estimation of the disease progression and mortality is vital for the management of the patients. Currently available image-based prognostic predictors for patients with COVID-19 are largely limited to semi-automated schemes with manually designed features and supervised learning, and the survival analysis is largely limited to logistic regression. We developed a weakly unsuper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“… TL? Scarpiniti, Sarv Ahrabi [ 68 ] A histogram-based 90.1 90.3 90.4 91 No No Perumal, Narayanan [ 69 ] CNN 92.3 91.5 92.6 93 No No Uemura, Näppi [ 70 ] GAN 95.1 95.4 96 95.3 No No Zhao, Xu [ 71 ] 3D V-Net 97.4 97.7 97.2 98.7 No No Hu, Huang [ 72 ] DNN 97.2 97.1 98.2 99 No No Toğaçar, Muzoğlu [ 73 ] CNN 97.6 97.3 98.1 99.1 No No Castiglione, Vijayakumar [ 74 ] ADECO-CNN 98.2 98.6 98.4 99 No Yes …”
Section: Resultsmentioning
confidence: 99%
“… TL? Scarpiniti, Sarv Ahrabi [ 68 ] A histogram-based 90.1 90.3 90.4 91 No No Perumal, Narayanan [ 69 ] CNN 92.3 91.5 92.6 93 No No Uemura, Näppi [ 70 ] GAN 95.1 95.4 96 95.3 No No Zhao, Xu [ 71 ] 3D V-Net 97.4 97.7 97.2 98.7 No No Hu, Huang [ 72 ] DNN 97.2 97.1 98.2 99 No No Toğaçar, Muzoğlu [ 73 ] CNN 97.6 97.3 98.1 99.1 No No Castiglione, Vijayakumar [ 74 ] ADECO-CNN 98.2 98.6 98.4 99 No Yes …”
Section: Resultsmentioning
confidence: 99%
“…As the diagnosis of COVID-19 using medical imaging has been a priority since the pandemic started, 39 (68%) of 57 studies reported the diagnosis of COVID-19 as the main focus of their work [ 19 - 21 , 23 - 33 , 35 - 37 , 39 , 41 , 42 , 44 , 46 , 50 , 52 , 53 , 55 , 56 , 58 - 60 , 63 - 69 , 71 , 72 ]. In addition, 9 (16%) studies reported data augmentation as the main task addressed in the work [ 18 , 43 , 45 , 49 , 54 , 61 , 62 ], 1 (2%) study reported prognosis of COVID-19 [ 22 ], 3 (5%) studies reported segmentation of lungs [ 34 , 51 , 57 ], and 1 (2%) study reported diagnosis of multiple lung diseases [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The augmented data were then used to improve the training of different CNNs to diagnose COVID-19. In addition, 3 (5%) studies used GANs for segmentation of the lung region within the chest radiology images [ 37 , 51 , 57 ], 3 (5%) studies used GANs for superresolution to improve the quality of the images before using them for diagnosis purposes [ 30 , 44 , 68 ], 5 (9%) studies used GANs for the diagnosis of COVID-19 [ 20 , 58 , 69 , 70 , 72 ], 2 (4%) studies used GANs for feature extraction from images [ 19 , 47 ], and 1 (2%) study used a GAN-based method for prognosis of COVID-19 [ 22 ]. The prevalent mode of imaging is the use of 2D imaging data, and 1 (2%) study reported a GAN-based method for synthesizing 3D data [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations